Modern evaluation of liquisolid systems with varying amounts of liquid phase prepared using two different methods - Vraníková, Barbora; Gajdziok, Jan; Vetchý, David (BioMed research international, 2015)
Liquisolid systems are an innovative dosage form used for enhancing dissolution rate and improving in vivo bioavailability of poorly soluble drugs. These formulations require specific evaluation methods for their quality assurance (e.g., evaluation of angle of slide, contact angle, or water absorption ratio). The presented study is focused on the preparation, modern in vitro testing, and evaluation of differences of liquisolid systems containing varying amounts of a drug in liquid state (polyethylene glycol 400 solution of rosuvastatin) in relation to an aluminometasilicate carrier (Neusilin US2). Liquisolid powders used for the formulation of final tablets were prepared using two different methods: simple blending and spraying of drug solution onto a carrier in fluid bed equipment. The obtained results imply that the amount of liquid phase in relation to carrier material had an effect on the hardness, friability, and disintegration of tablets, as well as their height. The use of spraying technique enhanced flow properties of the prepared mixtures, increased hardness values, decreased friability, and improved homogeneity of the final dosage form.
Keywords: Stearic Acids; Magnesium Compounds; Silicates; Rosuvastatin Calcium; rosuvastatin kalcium; sloučeniny hořčíku; polyethylenglykoly; silikáty; Polyethylene Glycols; laktosa; lidé; Lactose; Aluminum Compounds; Humans; sloučeniny hliníku; kyseliny stearové